2021
DOI: 10.3390/ma14226887
|View full text |Cite
|
Sign up to set email alerts
|

Bending Fracture of Different Zirconia-Based Bioceramics for Dental Applications: A Comparative Study

Abstract: The fabrication of fixed dental prostheses using aesthetic materials has become routine in today’s dentistry. In the present study, three-unit full zirconia fixed prosthetic restorations obtained by computer-aided design/computer-aided manufacturing (CAD/CAM) technology were tested by bending trials. The prostheses were intended to replace the first mandibular left molar and were manufactured from four different types of zirconia bioceramics (KatanaTM Zirconia HTML and KatanaTM Zirconia STML/Kuraray Noritake D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…To study the bending fracture of three-unit full zirconia fixed prosthetic restorations obtained by CAD-CAM technology, P. Fischer et al [11] performed bending tests on different types of zirconia bioceramic (KatanaTM Zirconia HTML and KatanaTM Zirconia STML/Kuraray Noritake Dental Inc.; NOVAZir® Fusion float® ml/NOVADENT/Dentaltechnik; and 3D PRO Zirconia/Bloomden Bioceramics). The three-unit full zirconia fixed prosthetics obtained were codified by K-H, N, B, and K-S respectively.…”
Section: Mechanical Properties Of Zirconia-based Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the bending fracture of three-unit full zirconia fixed prosthetic restorations obtained by CAD-CAM technology, P. Fischer et al [11] performed bending tests on different types of zirconia bioceramic (KatanaTM Zirconia HTML and KatanaTM Zirconia STML/Kuraray Noritake Dental Inc.; NOVAZir® Fusion float® ml/NOVADENT/Dentaltechnik; and 3D PRO Zirconia/Bloomden Bioceramics). The three-unit full zirconia fixed prosthetics obtained were codified by K-H, N, B, and K-S respectively.…”
Section: Mechanical Properties Of Zirconia-based Ceramicsmentioning
confidence: 99%
“…After the mechanical tests were performed, P. Fischer et al [11] emphasized that the bending strength of all three-unit dental prostheses tested is in correlation with the size, shape, and distribution of particles along with the presence of material defects. Nevertheless, the bending tests indicated that the highest forces at the failure values were registered for the B zirconia samples, followed by K-H and N samples, while the lowest values were obtained for the K-S specimens.…”
Section: Mechanical Properties Of Zirconia-based Ceramicsmentioning
confidence: 99%
“…Aesthetics plays a very important role in our society; as such, oral rehabilitation must take into account aesthetic requirements by using materials that meet the expectations of patients [ 11 , 12 ]. However, this should not compromise the strength, clinical success, and longevity of dental prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their aesthetic properties, there has been a substantial increase in the use of zirconia and ceramics in prosthetic rehabilitation [ 9 , 11 , 12 ]. This increase is due not only to the aesthetic component, but also due to these materials’ high fracture resistance and other mechanical properties [ 11 ], their excellent biocompatibility, and their physical properties [ 9 , 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation